Letter To Brezhnev - Gill, Alan (BFI, 2017)
"Eine junge Arbeitslose aus Liverpool verliebt sich in einen russischen Matrosen und findet dadurch die Hoffnung, aus ihrer tristen Umgebung ausbrechen zu können. Eine Einladung Breschnews ermöglicht ihr die Reise nach Rußland, zieht aber Konflikte in der Heimat nach sich. Modernes Märchen um die Macht der Träume und Liebe, die alle Barrieren überwinden kann, im Gewand einer größtenteils schwungvollen, milieugenauen Komödie." [filmdienst.de]
Original: Großbritannien 1985
Special features: presented in High Definition and Standard Definition ; an interview with Margi Clarke (2017, 35 mins) ; an interview with Alexandra Pigg and Peter Firth (2017, 14 mins) ; audio commentary with actor Margi Clarke ; audio commentary with Chris Bernard and Frank Clark ; From Liverpool with love (1985, 16 mins): original making-of documentary ; stills and collections gallery ; theatrical trailer ; illustrated booklet with new writing by screenwriter Frank Clarke and Professor Juliet Hallam, and full film credits
Keywords: Film